A kivándorlás és jólét összefüggése hazánkban az első világháború előtt és után - Koudela, Pál (Közép-Európai Közlemények, 2014)
Immigration policy of the United States of America right after the First World War altered basicly emigration from Hungary. Both its direction, volume and character changed but its impact on sending society is controversial. Decreasing emigration is evidently important but during the following 80 years migrational patterns remained mostly economic based. 1945, 1956 and 1989 caused high fluctuation but those peaks were only politically determined short periods thus real change occured only when Hungary accessed to the EU.